2011
DOI: 10.1186/2110-5820-1-42
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality in mechanically ventilated patients: comparison between NAVA and PSV modes

Abstract: BackgroundMechanical ventilation seems to occupy a major source in alteration in the quality and quantity of sleep among patients in intensive care. Quality of sleep is negatively affected with frequent patient-ventilator asynchronies and more specifically with modes of ventilation. The quality of sleep among ventilated patients seems to be related in part to the alteration between the capacities of the ventilator to meet patient demand. The objective of this study was to compare the impact of two modes of ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 30 publications
0
56
0
8
Order By: Relevance
“…13,14,19,48,49 In a recent comparison of the impact of NAVA and PSV on sleep architecture, we demonstrated that NAVA provided better sleep quality in terms of REM sleep, fragmentation index, and ineffective efforts in unsedated adults. 18 NAVA also allows considerable variability in the breathing pattern (ie, better replicates the variability of spontaneous breathing). We hypothesized that this greater variability, compared to PSV, decreased central apneas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,19,48,49 In a recent comparison of the impact of NAVA and PSV on sleep architecture, we demonstrated that NAVA provided better sleep quality in terms of REM sleep, fragmentation index, and ineffective efforts in unsedated adults. 18 NAVA also allows considerable variability in the breathing pattern (ie, better replicates the variability of spontaneous breathing). We hypothesized that this greater variability, compared to PSV, decreased central apneas.…”
Section: Discussionmentioning
confidence: 99%
“…18 We conducted a prospective, interventional, crossover study in a 22-bed medical ICU at Hôpital du Sacré-Coeur over a 12-month period. Inclusion criteria were invasive mechanical ventilation, normal consciousness, absence of sedatives and opiates for Ն 24 h, and PSV with an F IO 2 below 0.60 and a PEEP of 5 cm H 2 O to achieve an S pO 2 of at least 90%.…”
Section: Study Populationmentioning
confidence: 99%
“…Yoğun bakımdaki hastalarda uyku kalitesi uygun ventilatör ayarları sağ-lanarak ve hasta ventilatör uyumsuzluğu azaltılarak düzeltilebilir (31)(32)(33)(34)(35). Hasta ventilatör uyumsuzluğu solunum desteğini kısıtlayarak veya proportional asist ventilasyon (PAV) ve neurally adjusted ventilatory asist (NAVA) gibi modlar kullanılarak da düzeltilebilir (33,34).…”
Section: Uyku Ve Mekanik Ventilasyonunclassified
“…32,33 In a cohort crossover study, patients ventilated with NAVA had a higher proportion of REM sleep and less fragmented sleep. 34 …”
Section: Other Advantagesmentioning
confidence: 99%